Aeolian Material Transport and Its Role in Landscape Connectivity in the McMurdo Dry Valleys, Antarctica. Issue 12 (26th December 2018) - Diaz, Melisa A.; Adams, Byron J.; Welch, Kathleen A.; Welch, Susan A.; Opiyo, Stephen O.; Khan, Alia L.; McKnight, Diane M.; Cary, S. Craig; Lyons, W. Berry
Abstract: Arid regions, particularly polar and alpine desert environments, have diminished landscape connectivity compared to temperate regions due to limited and/or seasonal hydrological processes. For these environments, aeolian processes play a particularly important role in landscape evolution and biotic community vitality through nutrient and solute additions. The McMurdo Dry Valleys (MDV) are the largest ice‐free area in Antarctica and are potentially a major source of aeolian material for the continent. From this region, samples were collected at five heights ( 5, 10, 20, 50, and 100 cm) above the surface seasonally for 2013 through 2015 from Alatna Valley, Victoria Valley, Miers Valley, and Taylor Valley (Taylor Glacier, East Lake Bonney, F6 (Lake Fryxell), and Explorer's Cove). Despite significant geological separation and varying glacial histories, low‐elevation and coastal sites had similar major ion chemistries, as did high‐elevation and inland locations. This locational clustering of compositions was also evident in scanning electron microscopy images and principal component analyses, particularly for samples collected at 100 cm above the surface. Compared to published soil literature, aeolian material in Taylor Valley demonstrates a primarily down‐valley transport of material toward the coast. Soluble N:P ratios in the aeolian material reflect relative nutrient enrichments seen in MDV soils and lakes, where younger, coastal soils are relatively N depleted, while older, up‐valley soils are relatively P depleted. The aeolian transport of materials, including water‐soluble nutrients, is an important vector of connectivity within the MDV and provides a mechanism to help "homogenize" the geochemistry of both soil and aquatic ecosystems. Key Points: Polar and alpine deserts have diminished landscape connectivity due to limited and/or seasonal hydrological processes Connectivity of landscapes in the McMurdo Dry Valleys is more complex due to aeolian transport up to 100 cm above the surface Geochemistry of soluble salts and nutrients in aeolian material generally reflects complicated geologic and climate history of Ross Sea region